Targeting cholesteryl ester accumulation in the heart improves cardiac insulin response - Actis Dato, Virginia (2022)
Background: Antibodies against the P3 sequence (Gly1127-Cys1140) of LRP1 (anti-P3 Abs) specifically block cholesteryl ester (CE) accumulation in vascular cells. LRP1 is a key regulator of insulin receptor (InsR) trafficking in different cell types. The link between CE accumulation and the insulin response are largely unknown. Here, the effects of P3 peptide immunization on the alterations induced by a high-fat diet (HFD) in cardiac insulin response were evaluated. Methods: Irrelevant (IrP)- or P3 peptide-immunized rabbits were randomized into groups fed either HFD or normal chow. Cardiac lipid content was characterized by thin-layer chromatography, confocal microscopy, and electron microscopy. LRP1, InsR and glucose transporter type 4 (GLUT4) levels were determined in membranes and total lysates from rabbit heart. The interaction between InsR and LRP1 was analyzed by immunoprecipitation and confocal microscopy. Insulin signaling activity and glucose uptake were evaluated in HL-1 cells exposed to rabbit serum from the different groups. Findings: HFD reduces cardiac InsR and GLUT4 membrane levels and the interactions between LRP1/InsR. Targeting the P3 sequence on LRP1 through anti-P3 Abs specifically reduces CE accumulation in the heart independently of changes in the circulating lipid profile. This restores InsR and GLUT4 levels in cardiac membranes as well as the LRP1/InsR interactions of HFD-fed rabbits. In addition, anti-P3 Abs restores the insulin signaling cascade and glucose uptake in HL-1 cells exposed to hypercholesterolemic rabbit serum.